Bank Credit, Asset Prices and Financial Stability : Evidence From French Banks - Pouvelle, Cyril (Washington, D.C. : International Monetary Fund, 2012)
This paper analyses the effect of asset prices on credit growth in France and tries to disentangle credit demand and supply factors, both for the whole 1993-2010 period and during periods of financial instability. Using bank-level panel data at a quarterly frequency, stock price growth is shown to have a significant effect on lending growth over the whole period, but without credit supply factors being singled out. By contrast, housing price growth has a significant effect during periods of financial instability only, even after controlling for credit demand effects. These results show that credit demand factors do play a large role but also provide evidence of tighter credit constraints on households in financial instability periods.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet